Taurine: energy drink for T cells. - Bachmann, M (2012)
The activation of T cells causes many cellular changes, including alterations in cell morphology, motility, and size. While all immunologists know that T cells increase their size and become "blasted" upon activation, little attention has been paid to the question of how cell size is regulated and how this process influences T-cell responses. In this issue of the European Journal of Immunology, Kaesler et al. [Eur. J. Immunol. 2012. 42: 831-841] demonstrate that the organic osmolyte taurine and its transporter Taut are instrumental in driving cell-volume regulation and therefore the T-cell response. In the absence of Taut, effector and memory T-cell responses in mice are severely impaired, mainly due to increased apoptosis of effector cells. Hence, this paper provides an important link between the regulation of cell size and effector T-cell responses.